The Intersection between China's Belt and Road Initiative (BRI) and Indonesia's Global Maritime Fulcrum (GMF) after Covid-19 - Septyanto Galan Prakoso; Nadia Dian Ardita; Retnaningtyas Puspitasari; Ferdian Ahya Al Putra (UIN Sunan Gunung Djati, 2022)
In response to the current condition of political and economic conditions in Southeast Asia, this article will elaborate on the intersection between China’s and Indonesia’s foreign policy on two sides, negative and positive intersection by understanding the foreign policy vision of each country's policy. This study tries to explain the intersection of Belt Road Initiative (BRI) by China with Global Maritime Fulcrum (GMF) of Indonesia by using qualitative methods and collected data from library research. To deepen the understanding of how both states implemented their foreign policy, media analysis and national interest concept are used. The result indicates that Indonesia needs to respond to the foreign policy of China carefully. Moreover, the COVID-19 outbreak has altered the development of events on how the two missions from each country collide. Although every decision Indonesia has made regarding China’s BRI policy will not harm Indonesia’s national interest in the future, Indonesia will still have to tread carefully and imply wise decisions in its foreign policy, especially during the recovery period of COVID-19 pandemic.